Nilai-nilai sosial pada tari Kejei di desa Batu Ampar kecamatan Merigi kabupaten Kepahiang - Sriwulan, Febiola; Dewi, Desy Eka Citra; Yunarman, Sepri (MAN 4 Kota Pekanbaru, 2025)
This study explores the social values embedded in Tari Kejei, a sacred traditional dance of the Rejang ethnic community in Batu Ampar Village, Kepahiang Regency. The research aims to reveal the cultural meanings, moral lessons, and communal practices preserved through this dance amidst the challenges of globalization. Using a qualitative descriptive method, data were collected through observation, interviews, and documentation involving community leaders, dancers, and local residents. The findings indicate that Kejei dance reflects moral values such as cooperation and respect, aesthetic values through costumes, music, and symbolic movements, educational values fostering social responsibility and solidarity, and spiritual values rooted in gratitude and reverence for ancestors. Efforts to preserve the dance include establishing cultural studios, engaging youth, performing at local festivals, and utilizing social media. The study concludes that Kejei dance is not merely a performance but a medium for cultural continuity, social cohesion, and intergenerational identity transmission.